Fourier transforms : principles and applications - Hansen, Eric W. (Eric William), 1954- (John Wiley & Sons, 2014)
"Fourier Analysis with Complex Variables explains transform methods and their application to electrical systems from circuits, antennas, and signal processors--ably guiding readers from vector space concepts to the Discrete Fourier Transform (DFT) and the Fourier series. Featuring chapter end summaries of key results, over two hundred examples and four hundred homework problems, MATLAB files, and a Solutions Manual this book is perfect for graduate students in signal processing and communications as well as practicing engineers"--